THE PLIGHT OF ROHINGYA PEOPLE IN BANGLADESH: ACCESS TO JUSTICE AND HUMAN RIGHTS PROTECTION - Mahdi, Shyikh (Journal of Islamic Law Studies, 2018)
Bangladesh has a long history of hosting Rohingya from the Northern Rakhine State of Myanmar with the earliest arrivals recorded in 1948. The recent influxes occurred in last few years forced a large number of Rohingya to flee to Bangladesh in the wake of serious state repression in Myanmar. This huge influx of refugees without proper reception and attention from the Bangladeshi side caused severe humanitarian crisis; the appalling conditions of the refugee ghettos are gradually deteriorating. Desperate for their survival, the Rohingya people are infiltrating into various levels of socio-economic structures of Bangladesh without any proper plan/management policy. Often, Bangladesh is been used as the transit zone by the Rohingya people en route to other countries. The paper will analyze the existing situations of access to justice in formal and informal institutions by registered Rohingya Refugees in Cox’s Bazar District in Bangladesh. The specific objective of this paper is to make an assessment of existing situations of rights to access to justice, legal aid and representations, and fair trial of registered Rohingya residing currently in Bangladesh and check these in light of Bangladeshi national legal and international human rights standard. This paper will provide a thorough assessment of existing situation with a clear and precise analysis of international human rights and national legal standard. Some recommendations for improving the situation of Rohingya people for access to justice issue have been made at the end.